2017
DOI: 10.1039/c7ra02311a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced selectivity in the conversion of glycerol to pyridine bases over HZSM-5/11 intergrowth zeolite

Abstract: Intergrown zeolite HZSM-5/11(78) catalyst showed enhancement in the conversion of glycerol with ammonia to pyridine bases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In the previous experimental work, it was found that glycerol can be used as feedstock to be converted into pyridine with ammonia as the carrier gas and reactant . The optimal conditions for this synthesis process were achieved with HZSM-5 (Si/Al = 25) at 550 °C with a weight hourly space velocity (WHSV) of glycerol to the catalyst of 1 h –1 and ammonia to a glycerol ratio of 12:1 M. As shown in Figure , Previous literature suggested that glycerol need to undergo dehydration and a cracking process to produce various oxygenated compounds, such as acrolein, acetaldehyde, acetone, and acetol, which can be further converted into imines with the ammonia participation. ,,, These imines could be condensed to form cyclic compounds, including pyridine via Michael addition, dehydrogenation, deamination and dehydration reactions, etc. In the optimal condition, the partial product distribution using glycerol and other oxygenated compounds (including acetaldehyde and acrolein) as feedstocks can be seen in Table S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the previous experimental work, it was found that glycerol can be used as feedstock to be converted into pyridine with ammonia as the carrier gas and reactant . The optimal conditions for this synthesis process were achieved with HZSM-5 (Si/Al = 25) at 550 °C with a weight hourly space velocity (WHSV) of glycerol to the catalyst of 1 h –1 and ammonia to a glycerol ratio of 12:1 M. As shown in Figure , Previous literature suggested that glycerol need to undergo dehydration and a cracking process to produce various oxygenated compounds, such as acrolein, acetaldehyde, acetone, and acetol, which can be further converted into imines with the ammonia participation. ,,, These imines could be condensed to form cyclic compounds, including pyridine via Michael addition, dehydrogenation, deamination and dehydration reactions, etc. In the optimal condition, the partial product distribution using glycerol and other oxygenated compounds (including acetaldehyde and acrolein) as feedstocks can be seen in Table S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Pyridine is an aromatic heterocyclic compound with a nitrogen atom contained in it. It has several main derivatives, such as 2-methylpyridine, 3-methylpyridine, and 4-methylpyridine. , These pyridine rings, as the important raw material for the preparation of various intermediates, are widely useful in diverse applications, such as the market areas of agrochemicals, pharmaceuticals, vitamins, and other fine chemicals. , Traditionally, pyridine bases have been separated from the coal tar as one of the by-products by solvent extraction. , It is not a renewable method for the synthesis of pyridine. The present commercial feedstocks for the production of pyridines are carbonyl-containing compounds and ammonia or ammonia derivatives as the nitrogen source in the presence of various catalysts. These chemicals are also nonrenewable and are the by-products of fossil raw materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is observed that the intensity of (051) and (303) reflection, in 2h = 23.2°, 23.6°decrease, and (133) refection in 2h = 24.4°completely disappears which is a key feature of creation an intergrowth structure between ZSM-5 and ZSM-11 zeolites (Figure 1b). 39 However, with regard to diffraction at 2h = 238 it can be seen that the peak intensity has been reduced compared to ZSM-5/11 in metals modified zeolites especially after more loaded metals content (Zn-Cu-ZSM-5/11(2), Ga-Ag-ZSM-5/11 (2)) and this reduction in crystallite can occur due to higher absorption coefficient of loading metals or adding of metals during synthesis and the serious dealumination (Table 1). 40,41 Conforming to Debye-Scherer equation, the crystallite size of modified ZSM-5/11 zeolites, has been reduced, which are presented in Table 1.…”
Section: Xrd Characterizationmentioning
confidence: 99%